Identification of a novel β-adrenergic octopamine receptor-like gene (βAOR-like) and increased ATP-binding cassette B10 (ABCB10) expression in a Rhipicephalus microplus cell line derived from acaricide-resistant ticks. Issue 1 (December 2016) - Koh-Tan, H.; Strachan, Erin; Cooper, Katherine; Bell-Sakyi, Lesley; Jonsson, Nicholas
Abstract Background The cattle tickRhipicephalus (Boophilus )microplus is an economically important parasite of livestock. Effective control of ticks using acaricides is threatened by the emergence of resistance to many existing compounds. Several continuousR. microplus cell lines have been established and provide an under-utilised resource for studies into acaricide targets and potential genetic mutations associated with resistance. As a first step to genetic studies using these resources, this study aimed to determine the presence or absence of two genes and their transcripts that have been linked with acaricide function in cattle ticks: β-adrenergic octopamine receptor (βAOR, associated with amitraz resistance) and ATP-binding cassette B10 (ABCB10, associated with macrocyclic lactone resistance) in sixR. microplus cell lines, five otherRhipicephalus spp. cell lines and three cell lines representing other tick genera (Amblyomma variegatum, Ixodes ricinus andHyalomma anatolicum ). Methods End-point polymerase chain reaction (PCR) was used for detection of theβAOR gene and transcripts in DNA and RNA extracted from the tick cell lines, followed by capillary sequencing of amplicons. Quantitative real-time PCR (qPCR) was performed to determine the levels of expression ofABCB10 . Results βAOR gene expression was detected in allRhipicephalus spp. cell lines. We observed a second amplicon of approximately 220 bp for theβAOR gene in theR. microplus cell line BME/CTVM6, derived from acaricide-resistant ticks. Sequencing of this transcript variant identified a 36 bp insertion in theβAOR gene, leading to a 12-amino acid insertion (LLKTLALVTIIS) in the first transmembrane domain of the protein. In addition, nine synonymous SNPs were also discovered inR. appendiculatus, R. evertsi andR. sanguineus cell lines. Some of these SNPs appear to be unique to each species, providing potential tools for differentiating the tick species. The BME/CTVM6 cell line had significantly higherABCB10 (P  = 0.002) expression than the otherR. microplus cell lines. Conclusions The present study has identified a newβAOR gene and demonstrated a higherABCB10 expression level in the BME/CTVM6 cell line, indicating that tick cell lines provide a useful experimental tool for acaricide resistance studies and further elucidation of tick genetics.